Mythology gods and goddesses. (Mount Kisco, N.Y. Guidance Associates, 1981)
A two-part program that deals with both historical and literary aspects of mythology. It shows the nature of the Greek and Roman gods and of the importance of these gods in the lives of the ancient people. Emphasizes important stories introducing the principal figures in classical mythology.
Keywords: Mythology, Classical; Humanities